Экспериментальные исследования и разработки по регистрации индикатрис рассеяния света - Тихомиров И. А. Иван Арсентьевич; Мышкин В. Ф. Вячеслав Фёдорович; Цимбал В. Н.; Хан В. А. Валерий Алексеевич; Кемельбеков Б. Ж. (Томск, 1998)
Деп. в ВИНИТИ 12.05.98, № 1431-В98